2007
DOI: 10.1007/s00213-006-0651-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of test activity in ethanol-induced disruption of place preference expression in mice

Abstract: Disruption of ethanol-CPP observed in DBA/2J mice may be a consequence of high ethanol-induced activity levels. More generally, these studies suggest that competing behaviors can affect expression of a drug-induced CPP independent of affecting the conditioned rewarding effects of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
44
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 29 publications
13
44
4
Order By: Relevance
“…As in previous studies in DBA/2J mice (Gremel and Cunningham, 2007;Cunningham et al, 2006b), ethanol given immediately before the conditioning trial induced increases in locomotor activity (for group means and statistical comparisons, see Table 2). In experiment 1, lesions of the Amy only slightly reduced this ethanol-induced activation.…”
Section: Conditioning Activitysupporting
confidence: 69%
See 1 more Smart Citation
“…As in previous studies in DBA/2J mice (Gremel and Cunningham, 2007;Cunningham et al, 2006b), ethanol given immediately before the conditioning trial induced increases in locomotor activity (for group means and statistical comparisons, see Table 2). In experiment 1, lesions of the Amy only slightly reduced this ethanol-induced activation.…”
Section: Conditioning Activitysupporting
confidence: 69%
“…Although the differences in activity were relatively minor, subjects with Amy and Acb lesions showed higher levels of activity during the drug-free test. Although level of activation can affect preference (Gremel and Cunningham, 2007), we do not believe that the differences in activity observed in the present studies were sufficient to significantly alter the observed CPP because Acb-lesioned subjects expressed a preference similar to sham subjects. In summary, our data suggest that the Amy and Acb influence the acquisition of ethanol CPP, whereas the Amy modulates CPP expression.…”
Section: The Role Of the Acb And Amy In Locomotor Activitycontrasting
confidence: 59%
“…It is possible that even a subtle effect of D1/5 activation on locomotion could influence the effects on behavior. In the case of fear extinction and CPP extinction, any increase in activity would impact the expression of freezing or CPP (Gremel and Cunningham, 2007;Groblewski et al, 2009;Lattal and Maughan, 2012), which could be interpreted as an enhancement in extinction when it actually is an artifact of persistent locomotor effects. This is especially true in fear extinction, because activity is so suppressed that even a small effect on locomotion may reveal itself as an effect on freezing.…”
Section: Discussionmentioning
confidence: 99%
“…2. The dark and light conditions were studied in separate experiments in order to test mice under identical conditions within each experiment and to avoid comparisons between groups that differed in test session activity due to illumination differences (Gremel & Cunningham, 2007). For mice in the one-compartment groups, the left-right positions of the floor cues were randomly assigned for testing (counterbalanced within conditioning subgroups).…”
Section: Methodsmentioning
confidence: 99%